2018
DOI: 10.1007/s12070-018-1292-9
|View full text |Cite
|
Sign up to set email alerts
|

Mini Inferior Turbinoplasty-Tunneling Technique

Abstract: Techniques for inferior turbinate reduction vary with various surgical methods, which differ in the approach of preservation of tissue from total turbinectomy to limited submucosal cauterization. Our preferred method to address hypertrophic inferior turbinate by mini turbinoplasty-tunneling technique are presented. Critical steps include creation of window in the inferior turbinate with a 4 mm microdebrider blade and removal of both inferior turbinate mucosal hypertrophy and bony component to convert a convex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
1
4
0
1
Order By: Relevance
“…In agreement with another study which concluded that about 7% of patient who do Mini inferior turbinoplasty tunneling technique suffered from postoperative bleeding which were near to the results in this study. [9] Also another study reported that about 55% of patient who had Conventional partial inferior turbinectomy suffered from post-operative bleeding which were near to the results in this study. [8] There was significant difference between the two groups in the present study according to post-operative crustation which were more in group B (Conventional partial inferior turbinectomy) than group A (Mini inferior turbinoplasty tunneling technique).…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…In agreement with another study which concluded that about 7% of patient who do Mini inferior turbinoplasty tunneling technique suffered from postoperative bleeding which were near to the results in this study. [9] Also another study reported that about 55% of patient who had Conventional partial inferior turbinectomy suffered from post-operative bleeding which were near to the results in this study. [8] There was significant difference between the two groups in the present study according to post-operative crustation which were more in group B (Conventional partial inferior turbinectomy) than group A (Mini inferior turbinoplasty tunneling technique).…”
Section: Discussionsupporting
confidence: 69%
“…[2] Also another study reported that no need for anterior nasal packing after Mini Inferior Turbinoplasty Tunneling Technique. [9] There was significant difference between the two groups in the present study according to post-operative bleeding, in group A (Mini inferior turbinoplasty tunneling technique) was 5% and in group B (Conventional partial inferior turbinectomy) was 60%.…”
Section: Discussionmentioning
confidence: 44%
See 3 more Smart Citations